Structural studies on the hydration of L-glutamic acid in solution. - McLain, SE; Soper, A; Watts, A (2006)
A combination of neutron diffraction augmented with isotopic substitution and computer modeling using empirical potential structure refinement has been used to extract detailed structural information for L-glutamic acid dissolved in 2 M NaOH solution. This work shows that the tetrahedral hydrogen bonding network in water is severely disrupted by the addition of glutamic acid and NaOH, with the number of water-water hydrogen bonds being reduced from 1.8 bonds per water molecule in pure water to 1.4 bonds per water molecule in the present solution. In the glutamic acid molecule, each carboxylate oxygen atom forms an average of three hydrogen bonds with the surrounding water solvent with one of these hydrogens being shared between the two oxygen atoms on each carboxylate group, while each amine hydrogen forms a single hydrogen bond with the surrounding water solvent. Additionally, the average conformation of the glutamic acid molecules in these solutions is extracted.